Biological psychology - James W Kalat (Australia Cengage, 2019)
The most widely used text in its course area, James W. Kalat's BIOLOGICAL PSYCHOLOGY has appealed to thousands of students before you. Why? Kalat's main goal is to make Biological Psychology understandable to Psychology students, not just to Biology majors and pre meds--and he delivers. Another goal is to convey the excitement of the search for biological explanations of behavior. Kalat believes that Biological Psychology is "the most interesting topic in the world," and this text convinces many students--and maybe you, too--with clear writing, amusing anecdotes and intriguing examples. MindTap, an interactive online learning resource that integrates the text with videos, animations and a virtual bio-lab component, makes learning even easier and more enjoyable.